FAKTOR-FAKTOR YANG MEMPENGARUHI INTERAKSI MANUSIA DENGAN KOMPUTER PADA SISTEM INFORMASI BERBASIS JARINGAN DI KANTOR BALAI DIKLAT INDAG SURABAYA - Sonang Sitohang (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
This study examines the impact of interaction human factors with computer used by Local Area Network (LAN) at Regional Office Surabaya Industrial and Trade Training Service. The object of study are employees which worked by LAN Service office and used primary datas non probability sampling with analysis factor throught SPSS 10,0 windows program.The corelation matrix result shows of variable population; Barlets test of Sphericity (BTS) 0,000 proved, and Kayser Meyer Oklin (KMO) 0,671 > 0,50 means sample strength enough. By rotation from 35 variables become 22 variables with cumulative percentation 64,67. Tools is the dominant factor impact of human computer interaction by Local Area Network (LAN). The contribution of variable 10,187%, with eigen values 3,573 consist of; tools by loading variable 0,813, language with loading variable 0,745 and on line by 0,661 variable loading.